Older adults’ Internet use behavior and its association with accelerometer-derived physical activity - Chung, Yen-Yu; Chen, Jiaren; Lin, Mei-Chun; Liu, Ruo-Lan; Wu, Jenn-Bang; Tsai, Hsin-Chang; Lai, Ting-Fu; Liao, Yung; Park, Jong-Hwan (Frontiers in Public Health, 2025)
ObjectiveThe aging population is thriving worldwide, and it is critical to improve the health of older adults through physical activity (PA). Although the Internet can promote PA in older adults, limited studies have used objective tools to measure it. Thus, we aimed to investigate the association between the frequency of Internet use and PA levels in older adults.MethodsFor this cross-sectional study, we employed convenience sampling. The participants were 172 adults aged 65 and older without cognitive impairment who could walk independently. We measured PA using a triaxial accelerometer, step counts, and moderate-to-vigorous PA (MVPA). We measured Internet use via a self-report questionnaire, separated by frequency of use into high, moderate, and low or no use. We performed a one-way analysis of variance (ANOVA) and multiple logistic regression to examine the relationship between Internet use and PA.ResultsWe included a total of 172 older adults (72.0 ± 5.5 years; 78.5% female). The group that used the Internet with moderate frequency exhibited higher daily step counts than the group that used the Internet with low frequency or not at all (moderate frequency: 7,888 steps > low frequency or no use: 6,070.6 steps). Compared to the group that used the Internet at a moderate frequency, older adults with a low frequency or those who did not use the Internet were less likely to meet the recommendations of the World Health Organization (WHO) regarding PA [odds ratio (OR): 0.242; 95% confidence interval (CI): 0.077–0.751].ConclusionOlder adults with a low frequency of Internet use or those who did not use the Internet (i.e., those who used the Internet less than once a week or not at all, respectively) were less likely to meet the WHO’s recommended levels for PA than older adults who used the Internet with moderate frequency. The findings of this study can inform efforts to reduce age-related health risks and promote strategies for encouraging PA.